Correct and efficient UAV missions based on temporal planning and in-flight hybrid simulations - Pecker Marcosig, Ezequiel; Zudaire, Sebastián Alfredo; Castro, Rodrigo Daniel; Uchitel, Sebastian (Elsevier Science, 2023)
Fil: Pecker Marcosig, Ezequiel. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Investigación en Ciencias de la Computación; Argentina